Late Cytomegalovirus Infection in Kidney Transplant Recipients after a Six-Month Prevention Protocol - Cunha, L (2019)
BACKGROUND: Despite a reduction in the incidence of cytomegalovirus (CMV) infections after kidney transplantation, less is known about late CMV infection in kidney transplant recipients. OBJECTIVE: To assess incidence of CMV infection in a cohort of patients under a high surveillance CMV prevention protocol and identify factors associated with late CMV infection. METHODS: Analysis of a consecutive cohort of 181 kidney allograft recipients between January 2012 and Aug 2015. CMV prevention-protocol consisted of 6-month universal prophylaxis and pre-emptive therapy for high-risk group (D+/R- or patients submitted to lymphocyte-depleting agent for induction or rejection treatment) and pre-emptive therapy for standard-risk group (D±/R+). Stopping valganciclovir was followed by CMV screening in the next two appointments. RESULTS: CMV infection was identified in 73 of 181 patients; the rate in high-risk group and standard-risk group was similar (p=0.443). However, in the latter group, the infection occurred mostly in the first 6 months. Late CMV infection occurred in 25 of 181 patients (5 of standard-risk group and 20 of high-risk group), after a median (IQR) of 253 (230.3-312.3) days after transplantation and 55 (41-89.5) days after the protocol period. Screening for CMV after valganciclovir discontinuation revealed 56% of late CMV infections. In high-risk group, D+/R- was associated with late CMV infection (HR 2.7, p=0.039) and in standard-risk group; lower age was associated with late CMV infection (HR 0.89, p=0.02). CONCLUSION: The incidence of CMV infection was similar to that reported in the literature. In high-risk patients, antigenemia surveillance during prophylaxis did not appear to reduce late CMV infections. Antigenemia screening after valganciclovir had limited results in the diagnosis of late CMV infection. D+/R- was associated to late CMV infection in high-risk group. Lower age appeared to influence late CMV infection in standard-risk group.